596 Physical rehabilitation in heart failure with reduced ejection fraction: are the cardiac implantable devices a barrier? (Balneo and PRM Research Journal, 2024)
Abstract: The development of implantable cardiac devices brought a spectacular improvement in the prognosis of the patients with heart failure with reduced ejection fraction, reducing the risk of sudden cardiac death by implanting a cardiac defibrillator, improving ventricular remodeling through cardiac resynchronization and, at the same time, increasing the patients' functional capacity, reducing decompensation episodes and hospitalization. Physical training at moderate exercise intensity is safe and effective in patients with heart failure and cardiac implantable devices; even if they have a severely impaired effort capacity, and device related issues, the assessment of the disease status and of the device parameters before the enrollment in the training program warrants the improvement of physical performance and disease outcomes without notable adverse events.